Elastomeric Thermal Interface Materials with High Through‐Plane Thermal Conductivity from Carbon Fiber Fillers Vertically Aligned by Electrostatic Flocking. (8th July 2014) - Uetani, Kojiro; Ata, Seisuke; Tomonoh, Shigeki; Yamada, Takeo; Yumura, Motoo; Hata, Kenji
<x xml:space="preserve">Abstract</x> Electrostatic flocking is applied to create an array of aligned carbon fibers from which an elastomeric thermal interface material (TIM) can be fabricated with a high through‐plane thermal conductivity of 23.3 W/mK. A high thermal conductivity can be achieved with a significantly low filler level (13.2 wt%). As a result, this material retains the intrinsic properties of the matrix, i.e., elastomeric behavior. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>